Sistema de microscopia com multi-pontas : força atômica e campo próximo - Suárez, Vanessa Isabel Tardillo (2012)
In this work we made a review of how a multi-probes microscope using Atomic Force and Near Field Scanning Microscopy works. Currently, the Nanonics Multiview 4000 instaled at the Materials Caracterization and Microscopy Laboratory (LCMMAT) is not completly working. Nowadays, we are able to do Atomic Force Microscopy (AFM) and reflection and transmission Scanning Near Field Microscopy (SNOM) measurements. This kind of microscope have three probes which are able to do simultaneaous mesurements of AFM, C-AFM, SNOM, Raman Microscopy and nanolitography. It is the first multi-probe microscope to be instaled in Latin America. This work consists in studying the structure of this kind of microscope, how does it make AFM and SNOM measurements and how to analise them. We study the different electronic circuits which are used in this kind of microscopes and we compare both optical and tuning-fork feedback. It was explain step by step how to do and AFM and SNOM measurement. We study the processing and analise of this measurements. Finally, we made some different measurements using this tecniques. Some of this measurements were compared with that found in references in order to try to find some possible aplications which could be useful for future researches at our laboratory.